Heuristic-Based Usability Evaluation of Investment and Integrated Service Office Website - Pratiwi, Andita Suci; Maulana, Dicky; Ariannor, Wahyudi (STMIK Banjarbaru, 2024)
The Hulu Sungai Selatan Regency Investment and One-Stop Integrated Services Service (DPMPTSP) has been providing website-based information services up to the present. However, since its inception for public use, the DPMPTSP website has never undergone a user experience (UX) evaluation, thus making it difficult to ascertain whether the application fulfills users' desires and needs. This research aims to evaluate the usability of the DPMPTSP website using the heuristic evaluation method, which involves expert evaluators. The assessment results indicate that most usability aspects received positive evaluations. Nonetheless, some aspects scored poorly, such as the utilization of help buttons, system interaction following an error occurrence, and various other factors. Recommendations for improvement have been provided for each aspect, including enhancing consistency in icon selection and design, incorporating explanatory buttons, considering menu hierarchy for improved navigation flexibility, and refining error messages and help explanations. This research offers a comprehensive analysis of the DPMPTSP website's usability while also presenting guidance for enhancing the user experience and the website's effectiveness.Keywords: User Experience; Heuristic Evaluation; Usability Testing; Government Website; Improvement RecommendationsÂ AbstrakPada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Hulu Sungai Selatan (DPMPTSP) telah menerapkan layanan informasi berbasis website hingga sekarang. Namun, sejak diimplementasikan ke masyarakat, website DPMPTSP belum pernah dilakukan evaluasi User Experience (UX), sehingga belum dapat diketahui apakah aplikasi sudah sesuai dengan keinginan dan kebutuhan pengguna. Penelitian ini mengevaluasi usability dari website DPMPTSP menggunakan metode Heuristic Evaluation. Evaluasi melibatkan evaluator ahli. Hasil penilaian menunjukkan bahwa sebagian besar aspek usability mendapatkan penilaian positif. Namun, beberapa mendapatkan skor rendah, seperti dalam hal penggunaan tombol bantuan, interaksi dengan sistem setelah terjadi kesalahan, dan beberapa aspek lainnya. Rekomendasi perbaikan diberikan untuk masing-masing aspek seperti meningkatkan konsistensi dalam pemilihan ikon dan desain, menambahkan tombol-tombol penjelasan, mempertimbangkan tingkatan menu untuk fleksibilitas navigasi, serta memperbaiki pesan kesalahan dan penjelasan dalam bantuan. Penelitian ini memberikan pandangan yang mendalam mengenai usability website DPMPTSP, serta memberikan arahan untuk meningkatkan pengalaman pengguna dan efektivitas website tersebut.Â